Madrasah 5.0: Sinergi Nilai Islam, Kecerdasan Buatan, dan Manajemen Partisipatif - Dwiyama, Fajri (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
This article aims to explore the transformation model of madrasah management through the integration of Islamic values, artificial intelligence (AI), and participatory management in responding to the challenges of Society 5.0. Using the systematic literature review (SLR) method, this study analyzed 45 selected publications from the Scopus database, ERIC, and Islamic education journals (2018–2023). The results of the study show that the concept of